EFEKTIFITAS PERBEDAAN EFEKTIFITAS TERAPI AKUPRESUR DAN MUSCLE STRETCHING EXERCISE TERHADAP INTENSITAS NYERI PADA REMAJA PUTRI DENGAN DISMENORE - Nurhayati Wahyu Trianingsih; Tjahjono Kuntjoro; Sri Wahyuni (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2016)
The incidence of prim ary dysmenorrhea in Balikpapan Baru Hospital in December 2014 - March 2015: 7 people. The incidence of primary dismenore in MA Ash-Shifa Balikpapan from March to May, 2015 by 86% to 53.3% which led to disruption of activity. Efforts have been made is taking pain medication or herbal drink, rest, warm compresses and use white wood, but do not use acupressure therapy and muscle stretching exercise To prove the effectiveness of acupressure and muscle stretching exercise on pain intensity in adolescents with dysmenorrhea This is a quasi experimental study with two group comparison pretest and posttest design, a population of 60 and samples were 42 respondent. Instrumen Research is a questionnaire that is Numeric Rating Scale (NRS). Data were analyzed using paired t test and Mann Whitney Indicates there is a difference of pain before and after the intervention of acupressure and muscle stretching exercise with p value of 0.0001. There is a difference between group difference in pain acupressure and muscle stretching exercise with p value 0, 008. Acupressure therapy is more effective in reducing the intensity of menstrual pain (dysmenorrhea) in adolescent girls than muscle stretching exercise The need for educational institutions to improve the program UKS especially reproductive health services in the prevention of primary dysmenorrhea with acupressure and stretching muscle exercise and the need for health care institutions in the development of PIK-KRR particularly the handling of student dysmenorrhea with acupressure and muscle stretching exercise.